Steady state cyclic behaviour of a half-plane contact in partial slip subject to varying normal load, moment, shear load, and moderate differential bulk tension. (January 2020) - Andresen, H.; Hills, D.A.; Barber, J.R.; Vázquez, J.
Abstract: A new solution for a general half-plane contact in the steady state is presented. The contacting bodies are subject to a set of constant loads – normal force, shear force and bulk tension parallel with the interface – together with an oscillatory set of the same quantities. Partial slip conditions are expected to ensue for a range of these quantities. In addition, the line of action of the normal load component does not necessarily need to pass the centre-line of the contact, thereby introducing a moment and asymmetry in the contact extent. This advancement enables a mapping to be formalised between the normal and tangential problem. An exact and easy to apply recipe is defined.